Public health spending and childhood mortality in Sub-Saharan Africa - KAFIGA, Yusuph (KDI School, 2018)
This study examined direct and indirect impact of governance on childhood mortality in sub-Saharan Africa countries. Governance was measured by using two indexes which are government effectiveness and corruption index from World Bank Governance indicators. To determine the direct effect, government effectiveness and corruption indexes were treated separately while to determine the indirectly effect, government effectiveness and corruption indexes were interacted with public health expenditure. This empirical study uses longitudinal data sourced World Bank dataset covering 1995-2014 for 41 sub-Saharan countries depend on the availability of data on variables of interest. Under-five mortality rate was used as indicator for childhood mortality. To examine the impacts of governance on under-five mortality rate, we used fixed effect method. The study finds that government effectiveness has both direct and indirect strong effect in reducing rate of deaths of children below age five in sub-Saharan Africa. Moreover, study find improvement in water source, GDP per capita and AIDS/HIV prevalence all have statistically impact on under-five mortality rate. These findings corroborate previous related empirical evidence that governance has impact on reducing childhood mortality. These empirical estimates call for public health policy makers to take attention to the following; excellent public health services, political pressures, formulation and implementation of health policies and government commitment to health policies formulated.
Thesis(Master) --KDI School:Master of Public Policy,2018